Absolute clinical skill decay in the medical, nursing and allied health professions: a scoping review protocol. (June 2017) - Maehle, Valerie; Cooper, Kay; Kirkpatrick, Pamela
Abstract : Review questions/objectives: The objective of this scoping review is to examine and map absolute clinical skill decay in the medical, nursing and allied health professions and to map the range of approaches used to address decay of clinical skills in these professions. Specifically, the review questions are: which clinical skills, performed by which professional groups, are reported to be most susceptible to absolute clinical skill decay, and what approaches have been reported for addressing absolute clinical skill decay in the medical, nursing and allied health professions? In addressing the review questions, the following sub-questions will also be addressed: Which healthcare settings have been investigated in relation to addressing absolute clinical skill decay? What are the characteristics of the approaches used to address absolute clinical skill decay in the medical, nursing and allied health professions? Which outcomes have been utilized when investigating approaches to addressing absolute clinical skill decay? It is anticipated that this scoping review will inform further systematic review/s on the topic of addressing clinical skill decay in the medical, nursing and allied health professions, as well as identify gaps in the research knowledge base that will inform further primary research.